Funkcjonalność wychowawcza rodziny a ryzykowna aktywność młodzieży w Internecie - Kwiatkowski, Piotr; Jurczyk-Romanowska, Ewa (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The authors have made online risk behaviours of young persons the subject of their analysis. The behaviours pertained to: (1) online dating, (2) staying up all night to be online, (3), online “hating”, and (4) neglecting studying to be online. The research sample consisted of 674 students of diverse schools (secondary and vocational schools in the Dolnośląskie voivodship). The average age was 18.43 years. The research was conducted on the basis of the Pearson correlation analysis, multiple regression analysis, and factor regression analysis. On the basis of the conducted research it has been established that there is a statistically significant correlation between the tendency to engage in risk behaviours online and (1) externalisation problems, (2) sensation seeking, (3) a general tendency to engage in risk behaviour, that is, neurobehavioural disinhibition, as well as (4) the functionality of the family of origin, with a negative correlation with the latter.
Keywords: functionality of families; risk behaviour; neurobehavioral disinhibition; online activity